2015
DOI: 10.1007/s12185-015-1819-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of a microchip flow-chamber system as a screening test for platelet storage pool disease

Abstract: Platelet storage pool disease (SPD) is a platelet function disorder characterized by a reduction in the number or content of α-granules, dense granules, or both, and is diagnosed by specialized tests. Patients with SPD often present with prolonged bleeding time (BT), but the sensitivity and reproducibility of this test have limitations, often resulting in false negatives. It has recently been reported that an automated microchip flow-chamber system (T-TAS(®)) is useful in the assessment of anti-platelet therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…Interestingly, T-TAS also detected all patients with COX-like defects and secretion defects ( Figure 2D). This finding is consistent with earlier reports showing that T-TAS was able to detect all patients diagnosed with SPD [12]. T-TAS also showed high consistency in detecting abnormalities in patients with multiple defects.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, T-TAS also detected all patients with COX-like defects and secretion defects ( Figure 2D). This finding is consistent with earlier reports showing that T-TAS was able to detect all patients diagnosed with SPD [12]. T-TAS also showed high consistency in detecting abnormalities in patients with multiple defects.…”
Section: Discussionsupporting
confidence: 93%
“…T-TAS also showed high consistency in detecting abnormalities in patients with multiple defects. This finding supports the earlier report suggesting that T-TAS is reliable in detecting more severe forms of platelet defects such Bernard-Soulier syndrome [12]. However, T-TAS failed to detect thrombus formation in all patients with thrombocytopenia including three patients that gave normal responses by lumi-LTA (Figure 2A and 2B).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also, haplotype(s) of platelet GP polymorphisms have been described that affect the bleeding phenotype in VWD , and coinherited platelet function disorders may complicate the diagnosis and assessment of bleeding severity in VWD . In this respect, we have reported that the T‐TAS is highly sensitive to the defect in patients with platelet storage pool disease , and might be a good candidate as a screening test for a broad range of platelet function disorders. It is unclear, however, how the platelet GP haplotype modulates the T‐TAS results independently of VWF.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, we have recently described a novel microchip, whole‐blood, flow chamber procedure that automatically and reproducibly analyzes thrombus formation under various shear conditions. This total thrombus analysis system (T‐TAS ® ; Fujimori Kogyo, Yokohama, Japan) is easy to use and appeared to be useful for the screening and diagnosis of bleeding disorders including VWD and platelet function abnormalities . Furthermore, the occlusion times in T‐TAS correlated with bleeding score in type 1 VWD , suggesting that T‐TAS data could provide a good index of primary hemostasis, especially in different hemodynamic environments .…”
Section: Introductionmentioning
confidence: 99%